NLR, A Convenient Early-Warning Biomarker of Fatal Outcome in Patients With Severe Fever With Thrombocytopenia Syndrome - Wei, Yuanyuan; Wang, Zilong; Kang, Luyang; He, Lingling; Sheng, Nan; Qin, Jiangfeng; Ma, Shuangshuang; Xu, Honghai; Hu, Lifen; Zou, Guizhou; Gao, Yufeng; Li, Jiabin (Frontiers in Microbiology, 2022)
Background: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease, which poses a serious threat to public health. The purpose of this study is to examine the convenient early-warning biomarker of fatal outcomes in patients with SFTS to reduce mortality. Methods: A retrospective cohort study was performed on a cohort of patients with confirmed SFTS in the top two hospitals in Anhui Province, China. From 1 May 2016 to 31 October 2019, the clinical symptoms, laboratory indicators, and treatment data of patients with SFTS were evaluated, all patients with SFTS were followed up within 28 days after discharge unless died in the hospital. The laboratory indicators that could be used to predict the fatal outcome were identified. Results: 228 patients with SFTS were enrolled, the survival and death group was enrolled 177 and 51 patients, respectively. The median age of all 228 patients with SFTS was 63 years. Five laboratory indicators (SFTSV viral load, NLR, AST/ALT, ALT, and BUN) were enrolled in predicting the fatal outcome of patients with SFTS. The AUC of SFTSV viral load were highest (0.919), then NLR (0.849), followed by AST/ALT (0.758), AST (0.738), and BUN (0.709). The efficacy of SFTVS viral load and NLR in predicting fatal outcomes was brilliantly higher than AST/ALT, AST, and BUN. Kaplan-Meier survival curves were used to confirm that the case fatality rate was significantly increased in patients whose SFTSV viral load was higher than 500,000 or NLR higher than 2.0. Gamma-globulin treatment showed a significant difference between the survival group and the death group and the duration of gamma-globulin that had been proposed should not be less than 3 days. Conclusion: The SFTSV viral load and NLR showed great efficacy in predicting the fatal outcome of patients with SFTS, and NLR is a convenient early-warning biomarker that helps healthcare workers focus on patients with a high risk of a fatal outcome more efficiently. The efficacy of gamma-globulin provided a new idea for the treatment of SFTS, which needs further analysis in future studies.